POLYCYTHEMIA RISK IN NEONATES WITH DELAYED CORD CLAMPING - Wulandari Pramana, I Gusti Agung Ayu Sri; Putera Kemara, Ketut; Megadhana, I Wayan (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Delayed Cord Clamping is still a controversial issue in the world of medicine. Until recently, the perfect times to do a Delayed Cord Clamping in various parts of the Earth in the world are still very diverse. There are a few things that became a major concern associated with Delayed Cord Clamping, one of which is the increase in blood volume due to an increase in the number of erythrocytes which led to occurrence of neonatal polycythemia which later can lead to various complications. Polycythemia in neonates is a situation where the value of venous blood hematokrit over 65% (0.65) or the amount of hemoglobin more than 22gr/Dl. However, to date the data from a variety of the latest research and analysis of the studies mention that the polycythemia that occurs in neonates with umbilical cord pinching the flush delay was mild polycythemia that can improve after 48 to 72 hours after the baby is born.
Keywords: Polycythemia, Delayed Cord Clamping